Analysis of the Asymmetric Causal Relationship between Oil Prices, Oil Consumption and Environmental Degradation in Kazakhstan - Kudabayeva, Lyazzat; Imanova, Mehriban; Zurbayeva, Aliya; Mussaeva, Gulnar; Abubakirova, Aktolkin (International Journal of Energy Economics and Policy, 2025)
This study aims to analyze the asymmetric causal relationships between oil prices (OP), oil consumption (OC) and environmental degradation (CO2 emissions) in the context of the Kazakh economy. In this context, the asymmetric causality test developed by Hatemi-J (2012) was applied using annual data for the period 1993-2024. The study presents findings that can guide policy makers in the axis of energy economy and environmental sustainability. The results obtained revealed that there is no significant causal relationship between oil prices and oil consumption in any direction. This finding shows that price fluctuations have a limited effect on consumption behavior. On the other hand, a significant causal relationship between oil consumption and environmental degradation, operating through bidirectional and negative shocks, was determined. This situation shows that reductions in energy consumption lead to environmental improvements and that environmental regulations can also have an effect on energy consumption. An asymmetric structure was observed in the relationship between oil prices and environmental degradation. Positive (negative) shocks in oil prices cause positive (negative) shocks in CO2 emissions; however, shocks in emissions do not have a significant effect on prices. The general findings of the study emphasize that energy and environmental policies should not be designed independently of each other, but in interaction; and point to the necessity of a holistic policy approach in line with sustainable development goals.